2024
DOI: 10.1039/d3fo04806c
|View full text |Cite
|
Sign up to set email alerts
|

Integrated gut microbiome and metabolome analysis reveals the inhibition effect of Lactobacillus plantarum CBT against colorectal cancer

Yan-Yan Chen,
Fei Fei,
Ling-Ling Ding
et al.

Abstract: The microecological stability of the gut microbiota plays a pivotal role in both preventing and treating colorectal cancer (CRC). This study investigated whether Lactobacillus plantarum CBT (LP-CBT) prevents CRC by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Moreover, butyrate was shown to inhibit gastric tumors by reducing the expression of immunosuppressive factors, such as PD-L1 and IL-10 ( 87 ). In the context of colorectal cancer, a recent study demonstrated that oral administration of Lactobacillus plantarum CBT could effectively inhibit the growth of colorectal cancer in noth orthotopic as well as ectopic preclinical mouse models ( 88 ). Given the evidence that MH could effect changes in gut microbiota content, it would be extremely beneficial to characterize the relative changes in the metabolite abundance with a view of uncovering their influence on cancer growth and response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, butyrate was shown to inhibit gastric tumors by reducing the expression of immunosuppressive factors, such as PD-L1 and IL-10 ( 87 ). In the context of colorectal cancer, a recent study demonstrated that oral administration of Lactobacillus plantarum CBT could effectively inhibit the growth of colorectal cancer in noth orthotopic as well as ectopic preclinical mouse models ( 88 ). Given the evidence that MH could effect changes in gut microbiota content, it would be extremely beneficial to characterize the relative changes in the metabolite abundance with a view of uncovering their influence on cancer growth and response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus , known for its positive influence on colonic barrier function, prevents cytokine-induced apoptosis of intestinal epithelial cells and increases Muc2 mRNA levels in vitro . Several studies have reported that interventions with probiotics, prebiotics, and postbiotics can significantly increase the abundance of Lactobacillus in the gut microbiota of mice. A high proportion of Bacteroidetes is associated with colitis resistance and low-grade systemic inflammation . Previous research has demonstrated that Enterorhabdus, which exhibited a negative correlation with pro-inflammatory cytokine levels, contributed positively to intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Following sample homogenization, the filtrate was detected with the Thermo Vanquish (VQ-CORE-ISO-01, Thermo Fisher Scientific, USA) ultrahigh performance liquid chromatography system and the Thermo Orbitrap Exploris 120 mass spectrometry detector (BRE725531, Thermo Fisher Scientific, USA) equipped with an electrospray ion source (ESI). The detailed procedures can be found in the work by Chen et al in 2024 …”
Section: Methodsmentioning
confidence: 99%
“…The detailed procedures can be found in the work by Chen et al in 2024. 18 Statistical Analysis. All the statistical analyses were conducted using GraphPad Prism version 8.0.1.…”
Section: ■ Introductionmentioning
confidence: 99%